2021
DOI: 10.1017/jfm.2021.706
|View full text |Cite
|
Sign up to set email alerts
|

The influence of background turbulence on Ahmed-body wake bistability

Abstract: The discovery of wake bistability has generated an upsurge in experimental investigations into the wakes of simplified vehicle geometries. Particular focus has centred on the probabilistic switching between two asymmetrical bistable wake states of a square-back Ahmed body; however, the majority of this research has been undertaken in wind tunnels with turbulence intensities of less than $1\,\%$ , considerably lower than typical atmospheric levels. To better simulate bistability under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…(2020) and Burton et al. (2021) for an Ahmed body subjected to the -instability. It is found that the turbulent intensity magnitude does not affect the steady instability strength, and increases the switching rate of the mirror states in the bi-stable dynamics for values larger than 5 %.…”
Section: Introductionmentioning
confidence: 97%
“…(2020) and Burton et al. (2021) for an Ahmed body subjected to the -instability. It is found that the turbulent intensity magnitude does not affect the steady instability strength, and increases the switching rate of the mirror states in the bi-stable dynamics for values larger than 5 %.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, the nearwake flow with a higher blockage ratio is more turbulent. For the wake bi-stability behind the squareback Ahmed body, Burton et al (2021) have proved that a high turbulence level of the background flow leads to highly frequent switches. Moreover, for the squareback Ahmed body, He et al (2022) found that a higher TKE in the wake produced by a higher Reynolds number results in highfrequency wake switches, presenting a symmetric phenomenon.…”
Section: Physics Of Fluidsmentioning
confidence: 99%
“…The occurrence of such rapid switches reveals a high sensitivity of the wake (Haffner et al, 2020), as the asymmetric state stability is maintained by a weak interaction between underbody flow and the wake (Plumejeau et al, 2020). In many previous experimental studies (Grandemange et al, 2013a;Cadot et al, 2015;Varney, 2020;Burton et al, 2021;and He et al, 2022), limited by high sampling intervals or the use of filtering to remove highfrequency sampling noise, certain short-time switches were usually omitted. As identified by Volpe et al (2015) in their experiments on squareback Ahmed body, the calculated mean duration dT ƃ of the two stable positions decreased from 1092 to 421 when the resampling interval Dt ƃ s was reduced from 92.7 to 4.6.…”
Section: A Detection Of Wake Bi-stability and Corresponding Wake Topo...mentioning
confidence: 99%
“…As a result of the randomness of the long-time dynamics, the symmetry breaking position of case nW and wW happens to predominate on the right side (state R) in the current time window. Such statistical asymmetry induced by insufficient acquisition time is very common in the literature(Grandemange et al, 2013a;Cadot et al, 2015;Dalla Longa et al, 2019;Pavia et al, 2020;Plumejeau et al, 2020;Kang et al, 2021;Burton et al, 2021;and Bao et al, 2022) when bi-stability is involved. This is because achieving perfect statistical symmetry requires a recording time of over 60 times the long timescale T l $ 10 3 H=U 1(Volpe et al, 2015), which is time costly even for experiments.…”
mentioning
confidence: 99%